2000
DOI: 10.1002/(sici)1521-4079(200002)35:2<151::aid-crat151>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Charge Distribution of InGaZnO4. X-ray Diffraction Study of 20kb Single Crystal and 50kb Twin by Reticular Merohedry

Abstract: Cryst. Res. Technol. 352000 2 151-165Synthesis of InGaZnO 4 at 20Kb and 50Kb produced a single crystal and a twinned crystal respectively. The X-ray diffraction crystal structure refinement (R1 = 0.015 and 0.019 respectively) and the Charge Distribution analysis are reported. Space group is  R3m; cell parameters in hexagonal axes are a = 3.2990 (2)Å, c = 26.1013(25)Å (20kb single crystal) and a = 3.3051(2)Å, c = 26.1029(19)Å (50kb twinned crystal). The cell volume is 246.01(3)Å 3 and 246.94(3)Å 3 respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…These lattice planes correspond to the alternating layers of indium oxide and gallium/zinc oxide shown in the CAAC unit cell (d). 16 The reduced peak height of the weakly aligned film is consistent with increasing breadth in v scans. The weak peak at 66 is a substrate artifact.…”
mentioning
confidence: 64%
“…These lattice planes correspond to the alternating layers of indium oxide and gallium/zinc oxide shown in the CAAC unit cell (d). 16 The reduced peak height of the weakly aligned film is consistent with increasing breadth in v scans. The weak peak at 66 is a substrate artifact.…”
mentioning
confidence: 64%
“…In the present contribution, we report about the synthesis and structural characterisation of compounds in the ZnOIn 2 O 3 -Ga 2 O 3 system. The compound InGaO 3 (ZnO) 2 could be obtained as single crystals, and to our knowledge it is the second single crystal study of such homologous compounds apart of LuFeO 3 (ZnO) m (m = 1, 4 -6) reported by Isobe et al [16,17]. In our study we were even able to locate the cation sites in the wurtzite block by X-ray diffraction and bond valence calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The binary R 2 O 3 ±MO and ternary R 2 O 3 ±A 2 O 3 ±MO or R 2 O 3 ±TiO 2 ±MO systems (R = In, Ga or a rare earth element; A = In, Ga, Fe, Al; M = Mg, Mn, Fe, Co, Cu, Zn, Cd) have been investigated to clarify the synthesis conditions, phase relations, and stabilities and magnetic properties (Kimizuka et al, , 1995Siratori, 1993;Iida et al, 1990;Nakamura et al, 1990Nakamura et al, , 1993aYamaguchi et al, 1991;Brown et al, 1999). Structural studies have considered both the local structure, through high-resolution transmission electron microscopy (HRTEM) and/or electron diffraction (Matsui et al, 1979;Matsui, 1980;Cannard & Tilley, 1988;Uchida et al, 1994;Ho È rlin et al, 1998;Li et al, 1997Li et al, , 1998Li et al, , 1999aLi, Bando, Nakamura, Kurashima & Kimizuka, 1999;Wolf & Mader, 1999), and the global one, through powder (Cannard & Tilley, 1988;Cava et al, 1998;Moriga et al, 1999) and single-crystal X-ray diffraction (Geller et al, 1975;Kato et al, 1975Kato et al, , 1976Malaman et al, 1975Malaman et al, , 1976Isobe et al, 1990Isobe et al, , 1991Isobe et al, , 1994Nespolo, Nakamura & Ohashi, 2000;Nespolo, Sato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Type I has the three basal MÐO bonds shorter than the two apical ones: the cation is still relatively close to the basal plane, and the bipyramid is not much distorted. Type II has the cation signi®cantly off-centred from the basal plane, towards one of the corners: one of the apical bonds is shorter and the other is longer than the three basal ones (Nespolo, Sato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%